GENDER HEGEMONY IN KATE CHOPINâS THE AWAKENING AND ZORA NEALE HURSTONâS THEIR EYES WERE WATCHING GOD : A COMPARATIVE STUDY - , RETNO WULANDARI, Prof. Dr. C Soebakdi Soemanto, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
American women play important roles in the nationâs development. However, they have not yet be the menâs equal. When one sex has higher position than another, and the higher-positioned sex imposes its interests to another through consent, gender hegemony happens. Gender hegemony, where man has higher position than woman, could lead into patriarchal system. In this situation, patriarchal system becomes hegemonic system that leads the womenâs subordination towards the men through civil society sustained with political society. The thesis is aimed to elaborate how gender hegemony is exercised in two different characters from different races in Kate Chopinâs The Awakening and Zora Neale Hurstonâs Their Eyes Were Watching God. It also discusses resistance conducted by the main characters to challenge the hegemony. Through the umbrella of comparative study, universality and locality are also discussed. The scope of this thesis covers social, cultural, and political conditions of the era in the novelsâ settings, which are at the end of 19 th century in Creole white society, and end of 19 th century and early 20 th century in black community in rural Florida. The analysis shows that in both novels gender hegemony exists, that leads the characters lost their own freedom and independence to determine their own destinies. Both of them become not more than status symbols of their husbands. This picture strengthens the portrait of American women in that era. Even though written by two different writers from different races and time, the novels have similarity, that is gender hegemony, and some universality, which are awareness, resistance, and higher needs finding. Locality that reveals in the novels includes the form of hegemony sustained by its intellectuals. In The Awakening, intellectualâs roles do not change